2018
DOI: 10.7324/japs.2018.8907
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and In vivo Anti-inflammatory Activities of Coptosapelta flavescens Korth Root’s Methanol Extract

Abstract: Coptosapelta flavescens Korth is a liana plant of the Rubiaceae family known in East Kalimantan as Akar Tambolekar or Akar Merung. Its anti-inflammatory activity has not been scientifically proven in vitro or in vivo. The current study aimed to prove the anti-inflammatory activity of C. flavescens root (CFR) methanol extract in vitro and in vivo. The anti-inflammatory activity of CFR methanol extract was evaluated in vitro by examining its ability to stabilize the membrane of hypotonicity-induced red blood cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 9 publications
(19 reference statements)
0
4
0
2
Order By: Relevance
“…46 Additionally, various commonly used NSAIDs work by inhibiting the activity of these enzymes or preventing lysis of the lysosomal membranes to block release of the proteases. 55,56 We noted that the aqueous root extract of L. cornuta exerted significant membrane stabilization activity in hypotonic and heat induced HRBC haemolysis. Our findings corroborate those observed by Leelaprakash et al 51 Our study suggests that the aqueous root extract of L. cornuta possesses phytochemicals that stabilise erythrocyte membranes and prevent lysis upon exposure to osmotic or heat stress.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…46 Additionally, various commonly used NSAIDs work by inhibiting the activity of these enzymes or preventing lysis of the lysosomal membranes to block release of the proteases. 55,56 We noted that the aqueous root extract of L. cornuta exerted significant membrane stabilization activity in hypotonic and heat induced HRBC haemolysis. Our findings corroborate those observed by Leelaprakash et al 51 Our study suggests that the aqueous root extract of L. cornuta possesses phytochemicals that stabilise erythrocyte membranes and prevent lysis upon exposure to osmotic or heat stress.…”
Section: Discussionmentioning
confidence: 88%
“…46 Additionally, various commonly used NSAIDs work by inhibiting the activity of these enzymes or preventing lysis of the lysosomal membranes to block release of the proteases. 55 , 56 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Catechin and epigallocatechin gallate from green tea may inhibit COX2 expression induced by 12-O-tetradecanoylphorbol-13-acetate, tumor promoters in rat skin, and COX activity in macrophages induced by lipopolysaccharides [9], [10]. Quercetin-3-methoxy-40-glucosyl-7-glucoside from Maytenus heterophylla was effective as antiinflammatory against carrageenan-induced paw edema in rats [11]. The previous study showed that R. pinnata contain flavonoids, so it is possible to develop it as anti-inflammatory.…”
Section: Resultsmentioning
confidence: 96%
“…Larutan uji terdiri dari 1 ml dapar fosfat pH 7,4 (0,15 M), 0,5 ml suspensi sel darah merah, 2 ml hiposalin dan 0,5 ml larutan sampel pada berbagai konsentrasi (Kosala et al 2018). b. Pembuatan larutan kontol positif Larutan terdiri dari campuran dapar fosfat pH 7,4 (0,15 M) sebanyak 1 ml, suspensi sel darah merah sebanyak 0,5 ml, hiposalin sebanyak 2 ml dan larutan aspirin berbagai konsentrasi sebanyak 0,5 ml (Kosala et al 2018). c. Pembuatan larutan kontrol negatif Larutan kontrol negatif terdiri 1 ml dapar fosfat pH 7,4 (0,15 M), 0,5 ml suspensi sel darah merah, 2 ml hiposalin dan 1 ml larutan isosalin (Kosala et al 2018)…”
Section: ) Persiapan Larutan Uji Dan Pengukuran Absorbansi a Pembuata...unclassified